INTRODUCTION TO IN VITRO CULTURE OF RHAPОNTICUM CARTHAMOIDES - Raizer, O.; Tagimanova , D.; Nagmetova , G.; Khapilina , O. (Eurasian Journal of Applied Biotechnology, 2024)
The article presents the results of studies on the introduction into in vitro culture of the valuable medicinal plant Rhaponticum carthamoides, growing in the territory of the Kazakhstan Altai. R. carthamoides - or maral root is a source of various biologically active compounds (flavonoids, polysaccharides, saponins, cumanins). This species is of particular value as a producer of ultra-high quantities of ecdysteroids, which have a hepatoprotective and hypoglycemic effect, acting as adaptogens. Currently, natural reserves of this species are sharply reduced due to increasing demand and, as a consequence, lead to the depletion of natural populations. Modern biotechnology methods make it possible to develop highly effective approaches for the propagation and preservation of R. carthamoides for subsequent introduction and expansion of the range of fodder and medicinal crops that meet the needs of agriculture, medicine and the food industry. Seeds collected from their natural habitats were used as research material. A seed sterilization protocol has been developed; it has been established that to obtain aseptic seedlings it is necessary to use a multi-stage sterilization protocol using various sterilizing agents. Surface-sterilized seeds were placed on MS and MS media containing ½ mineral salts with different hormonal compositions. The results showed that the percentage of seed germination varied depending on the hormonal status of the environment and ranged from 42.9 to 85.5%. Thus, the lowest percentage of germination was noted on the B0 medium option (½ MS) - 42.9%. The highest percentage of germination was in seeds on the B3 medium option (MS + 3 mg/l BAP + 3 mg/l kinetin) - 85.5%.